Offline Vehicle Tracking and Visualizing on Digital Maps - Halil AYDIN; Omer Faruk BAY (International Journal of Applied Methods in Electronics and Computers, 2016)
Tracking mobile objects has always attracted people’s interest and over time it has become a necessity to keep records of them. Various solutions have been developed to meet this need. In particular, the development of GPS and digital mapping system has contributed greatly to these solutions. The developed methods can be divided into two main categories as online and offline systems. Although the online systems provide advanced features, production and operating costs are quite high and have regular expenses. In this study, we propose a microcontroller based offline vehicle tracking system. The proposed system offers a practical, low cost and high capacity approach for vehicle tracking systems. The proposed system calculates the vehicle’s position and speed according to the signals gathered from GPS satellites and records them to an SD card continuously. The stored data, then, can be transferred to a computer easily whenever needed and the routes that the vehicle followed can be tracked on a digital map using google earth. Besides, some visualization technics like coloring routes with regards to time or speed intervals can be used for advanced analyses of the data. The proposed system allows the GPS data to be recorded as long as 3 months on a 4 GB SD card continuously.